Picolinic Acid, a Tryptophan Oxidation Product, does not Impact Bone Mineral Density but Increases Marrow Adiposity - Ding, Kehong (Exp Gerontol, 2020)
Tryptophan is an essential amino acid catabolized initially to kynurenine (kyn), an immunomodulatory metabolite that we have previously shown to promote bone loss. Kyn levels increase with aging and have also been associated with neurodegenerative disorders. Picolinic acid (PA) is another tryptophan metabolite downstream of kyn. However, in contrast to kyn, PA is reported to be neuroprotective and further, to promote osteogenesis in vitro. Thus, we hypothesized that PA might be osteoprotective in vivo. In an IACUC-approved protocol, we fed PA to aged (23-month-old) C57BL/6 mice for eight weeks. In an effort to determine potential interactions of PA with dietary protein we also fed PA in a low-protein diet (8%). The mice were divided into four groups: Control (18% dietary protein), +PA (700 ppm); Low-protein (8%), +PA (700 ppm). The PA feedings had no impact on mouse weight, body composition or bone density. At sacrifice bone and stem cells were collected for analysis, including μCT and RT-qPCR. Addition of PA to the diet had no impact on trabecular bone parameters. However, marrow adiposity was significantly increased in PA-fed mice, and in bone marrow stromal cells isolated from these mice increases in the expression of the lipid storage genes, Plin1 and Cidec, were observed. Thus, as a downstream metabolite of kyn, PA no longer showed kyn’s detrimental effects on bone but instead appears to impact energy balance.